Age-Specific Differences in Association Between Personality and Changes in Outing Behaviors During the COVID-19 Pandemic in Japan: Cross-Sectional Web-Based Questionnaire Survey - Kaori Yamaguchi; Takemi Akahane; Emi Yasuda; Manabu Akahane (Online Journal of Public Health Informatics)
Abstract BackgroundThe outbreak of COVID-19 in 2019 led governments worldwide to introduce various public health measures, which included restrictions on travel and public gatherings, effectively reducing the spread of the virus and associated mortality rates. In Japan, nonlegally binding restrictions on outings effectively curbed infections, as in other countries. However, the restrictions impacted lifestyles, including reduced physical activity, increased frailty, and overeating issues, beyond the effect of preventing the spread of infection. Various factors such as personality, age, and cultural norms influenced outing behavior during the pandemic, which varied by activity type. ObjectiveTo elucidate the association between personality traits and changes in outing behaviors during the COVID-19 pandemic, as well as to clarify age-specific differences in outing behaviors, focusing on different types of outings. MethodsA cross-sectional survey was conducted using a web-based questionnaire in January 2021, when Japan announced its second emergency declaration during the pandemic. Overall, 1236 participants were recruited, with an equal number of participants for each gender and 10-year age group. The survey included questions regarding changes in the frequency of three types of outings—medical institution visits, eating out, and traveling—in addition to participants’ personality traits, such as sociability and morality. Multinomial logistic regression analysis was performed to analyze the association between personality traits and changes in different outing behaviors. Stratified analysis by age group was also performed. ResultsThe findings revealed that 790 participants reported no change in medical institution visits, although the frequency of eating out and traveling decreased during the pandemic. Regarding an age-wise comparison, a higher percentage of older people reported no change in medical institution visits but reported a decrease in eating out and traveling than younger people. Multinomial logistic regression analysis stratified by age showed that sociable people were more likely to report a decrease in the frequency of medical institution visits and an increase in the frequency of eating out (odds ratio [OR] 1.92, 95% CI 1.36‐2.71, PP=P=P= ConclusionsWe examined various behavioral changes observed during the pandemic for different types of outings and their associations with personality traits, as well as differences between age groups. The findings could help promote an understanding of how to effectively communicate and engage in appropriate behaviors in public health emergency settings.